Immigration Economics by George J. Borjas: A Review Essay - Card, David; Peri, Giovanni (Journal of Economic Literature, 2016)
We review Immigration Economics by George J. Borjas, published in 2014 by Harvard University Press. The book is written as a graduate-level textbook, and summarizes and updates many of Borjas's important contributions to the field over the past thirty years. A key message of the book is that immigration poses significant costs to many members of the host-country labor market. Though the theoretical and econometric approaches presented in the book will be very useful for students and specialists in the field, we argue that the book presents a one-sided view of immigration, with little or no attention to the growing body of work that offers a more nuanced picture of how immigrants fit into the host-country market and affect native workers. (JEL A22, J11, J24, J31, J61, R23)